Financial distress risk and stock price crashes - Andreou, Christoforos K.; Andreou, Panayiotis; Lambertides, Neophytos (My University, 2021)
This study uses 462,678 monthly observations of US-listed firms for the period 1990–2018 to document a strong positive relationship between short-term changes in financial distress risk and future stock price crashes. This result is economically significant as a one interquartile increase of the main explanatory variable in any month increases the probability of a stock price crash by 8.33% relative to its mean value. The findings withstand controls for a large array of variables, firm-fixed effect estimations, and alternative definitions of distress and crash risk measures; they are also robust to a range of tests conducted to buttress against endogeneity concerns. The study conducts analyses demonstrating that the positive distress-crash risk relationship is driven by managerial opportunism that seeks to camouflage bad news that has an adverse effect on firms' economic fundamentals. Accordingly, the findings corroborate an agency theory explanation for the impact of distress risk on stock price crashes. This study offers practical insights to investors, who should be vigilant of a firm's distress risk, as sudden short-term increases underscore withheld negative information pertinent to crash risk problems.
Keywords: Firm-specific stock price crashes; Distress risk; Bad news hoarding; Bad news hoarding; Agency problems; Managerial opportunism; Financial analysts